In situ monitoring of ligand-to-metal energy transfer in combination with synchrotron-based X-ray diffraction methods to elucidate the synthesis mechanism and structural evolution of lanthanide complexes - Al-Tayyem, Ban H.; Müscher-Polzin, Philipp; Pande, Kanupriya; Yefanov, Oleksandr; Mariani, Valerio; Burkhardt, Anja; Chapman, Henry N.; Näther, Christian; Braun, Michael; Radke, Marvin; Waitschat, Steve; Beyerlein, Kenneth R.; et al. (Frontiers in Chemistry, 2025)
Despite wide application of lanthanide complexes in solar cells, light-emitting diodes and sensors, their crystallization mechanisms have not been studied in detail. Further investigations of this kind can lead to the development of targeted synthesis protocols and tailoring of their structure-related physical properties. In this work, the structural evolution during the synthesis of the luminescent [Tb (bipy)2(NO3)3] (bipy = 2,2′-bipyridine) complex is studied by monitoring the ligand-to-metal energy transfer through in situ luminescence measurements combined with synchrotron-based X-ray diffraction (XRD) analysis. These experiments reveal an interesting crystallization pathway involving the formation of a reaction intermediate that is dependent on parameters such as ligand-to-metal molar ratios. In addition, the structure of [Tb (bipy)2(NO3)3] is solved from serial crystallography data collected at a microfocused synchrotron X-ray beamline. This is an emerging technique that can be used to interrogate individual crystallites and overcome beam damage effects. The resulting structure is found to correspond to that determined by classical single crystal XRD, and a perspective on realizing future in situ measurements of this type is given. This work therefore describes multiple advancements combining crystallite-specific diffraction probes and in situ techniques to track the synthesis kinetics of luminescent materials.